2021
DOI: 10.3389/fonc.2021.633034
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Invasive Scoring System to Differential Diagnosis of Clear Cell Renal Cell Carcinoma (ccRCC) From Renal Angiomyolipoma Without Visible Fat (RAML-wvf) Based on CT Features

Abstract: BackgroundRenal angiomyolipoma without visible fat (RAML-wvf) and clear cell renal cell carcinoma (ccRCC) have many overlapping features on imaging, which poses a challenge to radiologists. This study aimed to create a scoring system to distinguish ccRCC from RAML-wvf using computed tomography imaging.MethodsA total of 202 patients from 2011 to 2019 that were confirmed by pathology with ccRCC (n=123) or RAML (n=79) were retrospectively analyzed by dividing them randomly into a training cohort (n=142) and a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Diagnosing ERAML is a challenge due to its similarity to benign and malignant tumors in this area, such as lipoma, leiomyoma, adrenal adenocarcinoma, renal cell carcinoma, and retroperitoneal liposarcoma [5]. The best imaging for diagnosing renal angiomyolipoma is CT and CTA [3.6] In Wang et al's study, CT features for differentiating RAML from liposarcoma, such as intratumoral linear vessels, aneurysmal dilation of intramural vessels, beak signs, hematomas, and discrete internal and intrarenal fatty tumors, are mentioned [7]. An MRI with CT can also help in diagnosing the connection of renal vessels with ERAML [8].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing ERAML is a challenge due to its similarity to benign and malignant tumors in this area, such as lipoma, leiomyoma, adrenal adenocarcinoma, renal cell carcinoma, and retroperitoneal liposarcoma [5]. The best imaging for diagnosing renal angiomyolipoma is CT and CTA [3.6] In Wang et al's study, CT features for differentiating RAML from liposarcoma, such as intratumoral linear vessels, aneurysmal dilation of intramural vessels, beak signs, hematomas, and discrete internal and intrarenal fatty tumors, are mentioned [7]. An MRI with CT can also help in diagnosing the connection of renal vessels with ERAML [8].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of differentiating between RCC and RAML, Computed tomography(CT) is generally effective due to the presence of significant adipose tissue in most renal angiomyolipomas, resulting in low signal on CT images. Nevertheless, when distinguishing RCC from RAML without adipose tissue, there is a substantial decrease in imaging efficacy [ 29 ]. For example, in the majority of cases of epithelioid RAML, there is a paucity or absence of fat content, leading to potential confusion with classical renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the optimal value of AUC, when the value was assigned to 10, the diagnostic accuracy reached 91.7%, which greatly improved the clinically diagnostic accuracy of ENKTCL and the effect of its differentiation with DLBCL. The score model is a new points-scoring system for disease diagnosis pioneered by our research team, and it has been reported in many of our SCI papers and recognized internationally ( 16 18 ).…”
Section: Discussionmentioning
confidence: 99%